The effect of facial attractiveness on micro-expression recognition - Lin, Qiongsi; Dong, Zizhao; Zheng, Qiuqiang; Wang, Su-Jing (Frontiers in Psychology, 2022)
Micro-expression is an extremely quick facial expression that lasts for 40-200 ms and uncontrollable facial movement reveals an emotion that a person tries to conceal. Though much more difficult to detect and recognize, micro-expression recognition is similar to macro-expression recognition in that it is influenced by facial features. Previous studies suggested that facial attractiveness could influence facial expression processing. However, it remains unclear whether facial attractiveness could also influence micro-expression recognition. Addressing this issue, this study tested 38 participants with two micro-expression recognition tasks in both the static and the dynamic contexts. Three different micro-expressions (positive, neutral, and negative) at two attractiveness levels (attractive, unattractive). The results showed that participants were significantly faster when judging micro-expressions on attractive as compared to unattractive faces, and the interaction between facial attractiveness and micro-expression was significant. Furthermore, happy expressions on attractive faces were recognized faster in both the static and the dynamic conditions, highlighting the advantage of happy expression recognition. Therefore, our results provided the first evidence that facial attractiveness could influence micro-expressions recognition in both the static and the dynamic contexts.